Balanced Scorecard - indicadores estratégicos de desempenho para concessionárias automobilísticas: um estudo de caso para rede de caminhões - Ferrari, Everton Alves (2012)
In times of significant and constant changes in the global scenario, specially the economic and technological development of emerging nations as China, the companies have increased their need for efficient management tools which can offer feedback from their operation, regarding flaws and problems faced trying to achieve their goal. According to data provided by Fenabrave, in 2010 the commercial vehicle fleet (trucks) was consisted of 2.743.496 units with a average life of 17.2 years. From 2006 to 2010, the registration and licensing of this kind of vehicle increased 109.26%. Such statistics make the automobile market (trucks) attractive to new vehicle manufacturers. However, to the existing companies already established, the definition of targets in order to achieve long term goals have become vital to the survival of the dealerships in such competitive markets. One management tool which has shown efficiency in connecting the adopted business strategy to the operation, defined by the budget, is the Balanced Scorecard. Through its indicators, the vehicle dealerships (trucks) are able to measure the performance related to the goals set. In order to propose performance indicators that are able to align the business strategy with the goals defined on the dealerships budget, the methodology adopted was a field research along a dealership network of a given brand, the dealership association and the manufacturers. The research highlights the actual management profile of the vehicle dealerships (trucks) and proposes a strategic general map and performance indicators, in the four perspectives of the Balanced Scorecard applicable to the sector